Reproducing Nutritional Knowledge in the Digital Ecosystem through Adolescent Counseling Practices - Mustika, Abellia Cluara Salza; Kawedar, Muhammad Haikal (Department of Sociology, Universitas Nasional (Indonesia), 2026)
In the digital society, nutritional knowledge is continuously reproduced through mediated interactions rather than transmitted linearly. This study examines how nutritional knowledge is reproduced in the digital ecosystem through adolescent counseling practices. Using a qualitative case study of two nutrition students participating in a public counseling competition themed “Healthy Eating as Fuel for Modern Adolescents,” the research explores how evidence-based dietary guidelines were translated into accessible messages for youth audiences. Despite limited preparation time and the absence of face-to-face rehearsals, coordination was conducted through digital communication, reflecting the mediated nature of contemporary knowledge production. The findings reveal three interconnected processes: academic reproduction of scientific references, communicative adaptation to adolescent discourse, and symbolic amplification through media exposure, including radio interviews. The study argues that adolescent counseling represents a socio-digital negotiation of meaning in which young nutrition educators actively reconstruct and legitimize healthy eating narratives within the digital ecosystem.